NORMA SANKCJONOWANA W PRAWIE KARNYM JAKO PRZYKŁAD NORMY PRAWNEJ NIE BĘDĄCEJ NORMĄ POSTĘPOWANIA - Pohl, Łukasz (Wydział Prawa i Administracji UAM, 2006)
The aim of the paper is a theoretical analysis of a legal concept proposed by Zygmunt Ziembiński that each legal norm is a norm of conduct. However, an analysis of norms the breach of which is sanctionable in penal law suggests that this concept needs a certain correction. Norms may be also breached by an unfree act or behaviour. Consequently, the criterion of free/unfree will, or free/unfree act should be considered in the sphere where blame, or guilt is determined rather than in the sphere formulating the criteria for norm-based, or norm-abiding conduct. The proposed correction is in line with the view in criminal law that a forbidden act is not conditioned by the occurrence of free will.
NORMS THE BREACH OF WHICH IS SANCTIONABLE AS AN EXAMPLE OF LEGAL NORMS NOT BEING A NORM OF CONDUCT